2013
DOI: 10.1890/13-0028.1
|View full text |Cite
|
Sign up to set email alerts
|

The role of transient dynamics in stochastic population growth for nine perennial plants

Abstract: Abstract. Most populations exist in variable environments. Two sets of theory have been developed to address this variability. Stochastic dynamics focus on variation in population growth rates based on random differences in vital rates such as growth, survival, and reproduction. Transient dynamics focus on short-term, deterministic responses to changes in the stage distribution of individuals. These processes are related: demographic variation shifts stage structures, producing transient responses, which then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 37 publications
5
52
0
1
Order By: Relevance
“…S1) highlights a role for stochastic fluctuations in size structure as a potentially important component of demographic variability, as has been recently emphasized (Ellis andCrone 2013, McDonald et al 2016). This finding agrees with two recent comparative studies based on matrix population models, which found that the variance in realized growth rates (λ t ) caused by fluctuations in size structure was often larger than the variance caused by fluctuations in vital rates (Ellis andCrone 2013, McDonald et al 2016). However, the constant fluctuations in size structure that are characteristic of populations in stochastic environments may cause realized growth rates (λ t ) to deviate from expectations based solely on vital rates (λ 1,t ).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…S1) highlights a role for stochastic fluctuations in size structure as a potentially important component of demographic variability, as has been recently emphasized (Ellis andCrone 2013, McDonald et al 2016). This finding agrees with two recent comparative studies based on matrix population models, which found that the variance in realized growth rates (λ t ) caused by fluctuations in size structure was often larger than the variance caused by fluctuations in vital rates (Ellis andCrone 2013, McDonald et al 2016). However, the constant fluctuations in size structure that are characteristic of populations in stochastic environments may cause realized growth rates (λ t ) to deviate from expectations based solely on vital rates (λ 1,t ).…”
Section: Discussionmentioning
confidence: 65%
“…Importantly, this LTRE method approximates only the variance of the asymptotic population growth rate associated with each year (i.e., the leading eigenvalue of each year-specific kernel or matrix, λ 1,t ). We present the LTRE decomposition of Var(λ 1,t ) in Appendix S5 (including additional methods) as a complement to our simulation results, because this captures the influence of demographic correlations in isolation from stochastic fluctuations in population structure, which can be a substantial source of variability in population growth (Ellis andCrone 2013, McDonald et al 2016). The variance of λ 1,t is a relevant but incomplete measure of stochastic population dynamics because at each time step λ t = λ 1,t × reactivity t (Ellis andCrone 2013, McDonald et al 2016).…”
Section: Effects Of Vital Rate Correlations On the Variance Of Populamentioning
confidence: 99%
“…Furthermore, these alternative measures were not always highly correlated with measures of maximum population decline (Appendix S2) which is consistent with other studies of transient demography that found measures of short‐term population decline are weakly correlated with measures of short‐term population gain (Stott et al . ,b; Ellis & Crone ). Our results therefore demonstrate a rich diversity of patterns among species in the rate, magnitude and ability to recover from declines in density following introductions of seeds.…”
Section: Discussionmentioning
confidence: 99%
“…; Crone et al . ; Ellis & Crone ). Thus, invading populations could potentially experience significant extinction risks due to stochastic events if transient growth rates reduce invading populations to (or maintain populations at) low density, despite a high asymptotic growth rate.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental perturbations or long-term climatic changes can affect several demographic parameters, and integrating these complex interactions to assess the viability of a population can be challenging (Katzner et al 2006, Nadeem andLele 2012). Matrix population models, the standard tool for the study of population dynamics (Morris et al 2002), may not offer reliable population projections if environmental conditions in the future deviate from the conditions during which data were collected , or if unobservable demographic processes such as transience and immigration affect population dynamics (Ellis and Crone 2013). Incorporating the environmental drivers of demographic parameters and demographic processes such as immigration into population projections may therefore improve forecasts and strengthen the practical relevance of population viability assessments.…”
Section: Introductionmentioning
confidence: 99%